Primary leiomyosarcoma in the colon: A case report. Issue 7 (February 2018) - Yang, Jing
Abstract: Rationale: Leiomyosarcoma (LMS) is a common type of soft tissue sarcoma. Primary colonic LMS in general is a very rare entity, accounting for 1% to 2% of gastrointestinal malignancies. Patient concerns: We report a case of 55-year-old female who presented with a sudden onset of sharp right lower quadrant abdominal pain. Electronic colonoscopy showed a normal lumen. However, an abdominal computed tomography scan revealed a mass of soft tissue attenuation inseparable from the ascending colon which appeared as a gastrointestinal stromal tumor (GIST). Diagnoses: It is important to diagnose LMS definitively by immunohistochemical profiling of smooth muscle actin, desmin, and CD34. Interventions: She underwent laparotomy and right hemicolectomy, and histology confirmed a colonic LMS. The patient received no oncological treatment after surgery. Outcomes: No recurrence or metastasis was observed at 5 months postoperatively. It is crucial to identify colonic LMS precisely based on immunohistochemistry, and thereby distinguish it from GIST. Lessons: Further investigation on LMS cases so far is required to establish standard treatment strategies.